Effects of rye cultivars and management intensity on volatile profile of rye-based spirit distillates. (November 2022) - Pielech-Przybylska, Katarzyna; Balcerek, Maria; Ługowoj, Szymon; Królak, Katarzyna; Dziekońska-Kubczak, Urszula; Kuta, Agnieszka; Rozbicki, Jan; Studnicki, Marcin
Abstract: Polish rye grain was cultivated at two levels of management intensity: moderate-input and intensive-input management. Neither the rye cultivar nor the management intensity had a statistically significant effect on the chemical composition of the tested rye grains. The management intensity of rye cultivation did not influence ethanol production. The real yield of absolute ethanol (A100 ) from 100 kg of the tested rye cultivars was 30.73 ± 0.52 L for KWS Serafino rye grain (intensive management) and 37.14 ± 0.34 L for Antonińskie rye grain (moderate management). However, the concentrations of all volatile compounds in the distillates were significantly affected by the rye cultivar. Management intensity influenced the concentration of almost all carbonyl compounds, excluding acetaldehyde. The differences in the concentrations of esters and higher alcohols were mainly associated with the rye cultivar. The effect of rye cultivar and management intensity, as well as their interactions, influenced the content of methanol and the majority of carboxylic acids. Graphical abstract: Image 1 Highlights: Rye cultivar and management intensity did not affect starch and protein content. Management intensity of rye cultivation did not influence ethanol production. Volatile compounds in the distillates were mainly determined by rye cultivars.